Voltage-dependent calcium channels - Dolphin, Annette (Henry Stewart Talks, 2007)
Introduction to voltage-gated calcium channels, Correlation of known structural features to function, Subtypes of calcium channels and their physiological correlates, Pharmacology of voltage-gated calcium channels, G protein modulation of certain subtypes of voltage-gated calcium channels, Calcium channelopathies